The Epidemiology of Leprosy in Peru - Pesce, Hugo (1961)
Our professional in southern Peru exercise brought us into contact in 1937 with an outbreak of leprosy Andean hitherto ignored and forced us to the study of leprosy in their clinical, epidemiological and sanitary aspects . A stay of nearly two years in Brazil and Argentina us . consented then receive valuable teaching these leprológicas schools and allowed us in 1944 to assume the responsibility of organizing in our country the National Leprosy . Got the help of a select group of national medical , through the joint efforts of a few decades Peruvian leprolóqico School who was able to assert its valimiento in different fields of specialty was born. Principal Clinical Associate Professor of Infectious , Parasitic and Tropical Diseases , and the Faculty of Medicine of Lima. Medical Officer , Division of Leprosy , Ministry of Public Health. Regular Member of the Panel of Experts Consulting Leprosy , World Health Organization .